Pengaruh Source Credibility, Trust, Parasocial Interacrion, dan Physical Attractiveness Terhadap Purchase Intention Konsumen Gen Z - Ajeng Devita Anugraini; Lia Amalia (As-Syirkah: Islamic Economic & Financial Journal, 2025)
Generation Z is increasingly influenced by social media when making purchasing decisions, particularly by influencers on platforms like Instagram. This study aims to analyze the impact of source credibility, trust, parasocial interaction, and physical attractiveness of influencer Tasya Farasya on the purchase intention of Generation Z consumers. The study employed a purposive sampling method involving 150 respondents aged 18 years and above. Data were collected through an online survey and analyzed using PLS-SEM with the assistance of SPLS 4 software. The results showed that source credibility, parasocial interaction, and physical attractiveness positively influence purchase intention, while trust does not have significant impact. These findings emphasize that the credibility and visual appeal of influencers play a critical role in driving the purchase decisions of Generation Z consumers. Form a practical perspective, companies are advised to collaborate with influencers who are credible and visually appealing to enhance the effectiveness of marketing campaigns.